2019
DOI: 10.5812/jssc.87534
|View full text |Cite
|
Sign up to set email alerts
|

Genital Darier’s Disease: A Case Report

Abstract: Introduction: Darier's in the gentital tract is an uncommon hereditary disease. Its clinical manifestation on the vulva is rare. Case Presentation: A 59 year old woman with dyspareunia and pruritus with verrocus papules on labia minor and major. Pap smear of cervix showed a low grade squamous intraepithelial lesion, but during a biopsy it was found to be vaginal involvement by Darier's disease. Conclusions: Some skin diseases such as Darier may involve vaginal tract and cervix and diagnosis need special consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They act by suppressing acantholysis and dyskeratosis; they also induce cell proliferation, keratinization, and immunomodulation, resulting in relief of the symptoms. Mansouri et al reported a case of a woman with hyperkeratotic papules on the vulva [ 15 ]. A skin biopsy was performed for the diagnosis, and the pathology report was consistent with Darier disease.…”
Section: Discussionmentioning
confidence: 99%
“…They act by suppressing acantholysis and dyskeratosis; they also induce cell proliferation, keratinization, and immunomodulation, resulting in relief of the symptoms. Mansouri et al reported a case of a woman with hyperkeratotic papules on the vulva [ 15 ]. A skin biopsy was performed for the diagnosis, and the pathology report was consistent with Darier disease.…”
Section: Discussionmentioning
confidence: 99%